Effect of collaborative learning based nutrition education on diet quality and nutrition knowledge among in-school adolescents in Ogun state Nigeria. - Ademiluyi, Dare D.; Ojo-Adalumo, Ayobami R.; Olubiyi, Esther D.; Ogunniyi, Akinade E. (Discover Public Health, 2026)
Background: Poor diet quality and inadequate nutrition knowledge during adolescence contribute to micronutrient deficiencies and increasing non-communicable disease (NCD) risk in low- and middle-income countries. Evidence remains limited on whether collaborative learning–based nutrition education improves objectively measured diet quality among adolescents in sub-Saharan Africa. This study evaluated the effect of a collaborative learning–based nutrition education intervention on diet quality and nutrition knowledge among in-school adolescents in Ogun State, Nigeria. Methods: A quasi-experimental pretest–posttest control group design was employed among 274 adolescents aged 13–19 years enrolled in private secondary schools. Participants were assigned to either a collaborative learning–based nutrition education intervention or usual didactic instruction over eight weeks. Diet quality was assessed using the Diet Quality Questionnaire (DQQ), generating Dietary Diversity Score (DDS), NCD-Protect, NCD-Risk, and Global Dietary Recommendations (GDR) scores. Nutrition knowledge was assessed using a validated questionnaire. Within- and between-group changes were analyzed using paired and independent tests, and analysis of covariance (ANCOVA) adjusted for baseline values and sociodemographic factors. Results: Compared with controls, the intervention group showed significantly greater improvements in NCD-Protect score (Δ = 3.03; p < 0.001), NCD-Risk score (Δ=−1.11; p < 0.001), and GDR score (Δ = 4.14; p < 0.001). Improvements in DDS were observed in both groups, with no significant between-group difference. Nutrition knowledge increased significantly in the intervention group (Δ = 9.39; p < 0.001). ANCOVA confirmed a strong independent intervention effect on GDR (ηp²=0.26) and nutrition knowledge (ηp²=0.13). Conclusion: Collaborative learning–based nutrition education was associated with significant short-term improvements in diet quality and nutrition knowledge among adolescents, and represents a promising school-based strategy for NCD prevention in settings undergoing dietary transition.